Outsourcing in startups. Issue 2 (8th June 2021) - Steinbruch, Fernanda Kalil; Fernandes, Bernardo Soares; Nascimento, Leandro da Silva; Zawislak, Paulo Antônio
Abstract : Purpose: The purpose of this paper is to identify the main activities that startups outsource and the elements involved in outsourcing decisions. Design/methodology/approach: A multi-case study composed of Brazilian startups was conducted. Data through interviews and secondary sources were obtained. Two groups of startups were considered and analyzed comparatively: startups in the development stage and in the sales stage. Findings: The findings show that even though the literature suggests that the core business should not be outsourced, some startups do have to outsource this kind of activity. That was the main difference found between startups in the sales stage and in the development stage: the former group has a solid structure, knowledge and resources, so they can keep the core business inside the firm; whereas the latter group has little experience, scarce knowledge and resources, making outsourcing a more attractive alternative. Originality/value: Theoretically, this paper approaches a perspective underexplored in the innovation and management literature: outsourcing in startups. It highlights how outsourcing, as a decision between making and buying, can help startups to improve success potential. In practice, this paper discusses and demonstrates why and what can be outsourced by startups in the development and in the sales stages to overcome their limitations and, consequently, achieve better innovative results.